Espacio de trabajo matemático idóneo de un profesor universitario con respecto a la derivada de una función real - Carrillo Lara, Flor Isabel (2022)
The teacher's work and practice in the classroom provide us with information about the mathematical workspaces that the mathematics teacher provides. In this research report we reflect on the ideal Mathematical Workspace (MWS) of a university professor. The ideal MWS is concerned with studying the mathematical activity that the teacher promotes in the classroom when working on a class session on the subject of the derivative. Based on the case study method as a valuable research tool, which records the teacher's behavior involved in the studied phenomenon.